Exploring potential of protected cultivation in India—a review (Current Horticulture, 2023)
Protected cultivation has become an integral part of modern agriculture, significantly contributing to global food security and  horticultural production. The diverse array of structures and crops grown under protection underscores the adaptability and  versatility of these systems. As the world grapples with the challenges of feeding a growing population, protected cultivation is set  to play an increasingly vital role in the future of agriculture, offering solutions to the problems of climate change, resource scarcity,  and food quality. To realize the full potential of protected cultivation, governments, agricultural institutions, and private sector must  work together to support and promote sustainable practices, ensure training and knowledge sharing, and create favourable policies  for its continued growth. Looking to the future, the potential of protected cultivation is enormous. As global population growth and  climate change continue to exert pressure on traditional agriculture, protected cultivation offers a sustainable solution to increase  food production, ensure crop quality, and reduce the dependency on seasonal variations. Additionally, technological advancements  in energy-efficient systems, renewable energy adoption, and integrated pest management are expected to make protected cultivation  even more sustainable and economically viable.
Keywords: Protected; economically